ANALYSIS OF THE REFORMS IMPLEMENTED IN THE HIGHER EDUCATION SYSTEM OF THE REPUBLIC (Scientific Journal of Actuarial Finance and Accounting, 2024)
The article analyzed the main directions of the reforms implemented in the higher education system of the Republic of Uzbekistan in recent years and their economic and social aspects. Radical changes in higher education, as a result of the implemented reforms, positive changes such as the increase in the number of higher education institutions and admission quotas have been shown. In addition, the article examines the problems and deficiencies encountered in the higher education system, as well as ways to solve them. Suggestions for the continuation and improvement of these reforms are given by the author.